Stroke care in the United Kingdom before, during, and after the COVID-19 lockdowns: A retrospective nationwide cohort study - Youssef Hbid; Kaili Stanley; Charles D. A. Wolfe; Ajay Bhalla; Martin James; Abdel Douiri (PLoS ONE, 2025)
Background and aim The COVID-19 pandemic imposed significant pressures on healthcare services such as stroke care. This study aimed to assess the quality of stroke care and, outcome before, during and post lockdown. Methods Nationwide registry-based cohort study of patients with acute stroke admitted to hospitals in England, Wales, and Northern Ireland were analyzed. This included 114 hospitals for study cohorts of 261,451 in the pre-pandemic control period (01/04/2017–25/03/2020). The exposures studied include 16,843 during the first lockdown (26/03/2020–23/06/2020), 48,004 during the second lockdown (05/11/2020-17/05/2021), and 82,732 post-lockdowns (18/07/2021–30/06/2022). Logistic regression was used to compare odds of receiving aspects of acute stroke care across pandemic periods compared to the pre-pandemic period. Survival after stroke was assessed using restricted mean survival time (RMST) analysis, with models adjusted for age, sex, and stroke severity. Results Admission to a stroke unit within 4-hours increased by 8% during the first lockdown but fell by 7% in the second lockdown and remained lower post-pandemic. During the first lockdown, brain imaging within 1-hour increased by 3%, but was not maintained thereafter. Stroke multidisciplinary access increased during the first lockdown but decreased in subsequent periods. Access to thrombectomy sequentially increased across time periods; by 40% during first lockdown (adjusted Odd-Ratio: 1.4; 95% CI:1.24–1.58), second lockdown (aOR: 1.77; 1.66–1.92), and 2-folds post-lockdown (aOR: 2.03; 1.92–2.15). Thrombolysis rates fell during the pandemic and did not recover post-pandemic. Although proportion of patients discharged with good recovery did not alter, 7-day mortality increased by 10% (hazard ratio: 1.10, 1.04-1.18) in the first lockdown period but improved thereafter. Conclusion This nationwide population data showed unprecedented levels of pressure from the COVID-19 pandemic which have had an enduring effect on the quality of hospital stroke care and patient outcomes. Stroke care has not fully recovered post-pandemic period suggesting limited resilience.